2021
DOI: 10.1128/aac.01916-20
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Genetic Basis of Pyrazinamide Resistance in Monoresistant Mycobacterium tuberculosis

Abstract: Pyrazinamide (PZA) is a widely used antitubercular chemotherapeutic. Typically, PZA resistance (PZA-R) emerges in M. tuberculosis strains with existing resistance to isoniazid and rifampicin (MDR) and is conferred by loss-of-function pncA mutations that inhibit conversion to its active form, Pyrazinoic acid (POA). PZA-R departing from this canonical scenario is poorly understood. Here, we genotype pncA and purported alternative PZA-R genes (panD, rpsA, and clpC1) with long-read sequencing of nineteen phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Of these isolates, 10 had unique insertions and 4 appeared to be siblings. Consistent with other recent studies ( 20 22 , 32 34 ), insertions were identified in the carboxy-terminal coding region of panD and in the promoter region of clpC1 ( Table S2 ). Eight additional unique insertions were identified within seven other genes ( Table S2 ), four of which we recently associated with PZA or POA resistance ( 35 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Of these isolates, 10 had unique insertions and 4 appeared to be siblings. Consistent with other recent studies ( 20 22 , 32 34 ), insertions were identified in the carboxy-terminal coding region of panD and in the promoter region of clpC1 ( Table S2 ). Eight additional unique insertions were identified within seven other genes ( Table S2 ), four of which we recently associated with PZA or POA resistance ( 35 ).…”
Section: Resultssupporting
confidence: 91%
“…Considering that most clinical PZA resistance is mediated by pncA mutations and an intact SigE regulon is essential for tolerating other antitubercular therapeutics ( 46 ), we reasoned that any enrichment for sigE mutants would be exceedingly rare and appear more frequently—if not exclusively—in pncA WT PZA-monoresistant isolates. Accordingly, we contrasted the prevalence of sigE mutations in a large global set of clinical isolates ( n = 1,215) to a recently curated set of PZA-monoresistant isolates ( n = 18) in which pncA WT isolates were markedly overrepresented ( 34 ), including three that are both pncA WT and panD WT . Among all isolates, six nonsynonymous sigE mutations were observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, as rpoB :I1106T/X were only carried by isolates from this cluster, it is uncertain whether the mutation truly improved fitness, or was simply a neutral mutation carried by the common ancestor of the outbreak. Monophyletic mutations can still effect phenotype 30 , however as with any association, follow-up mutagenesis is needed to show causation.…”
Section: Discussionmentioning
confidence: 99%
“…Monophyletic mutations can still effect phenotype 30 , however as with any association, follow-up mutagenesis is needed to show causation.…”
Section: Discussionmentioning
confidence: 99%
“…The main driver of clinical resistance to PZA is through development of mutations in the PncA encoding gene, pncA (18)(19)(20)(21)(22). Resistant mutants raised on high concentrations of POA in vitro, as well as roughly 10% of PZA-resistant clinical Mtb isolates, can also develop mutations in panD (23)(24)(25). The panD gene encodes for an aspartate decarboxylase which carries out the penultimate step in pantothenate biosynthesis, an essential precursor of coenzyme A synthesis.…”
Section: Introductionmentioning
confidence: 99%